Catfish spawning training and silkworm cultivation in Pelita Jaya Village Indonesia - Soetignya, Widadi Padmarsari; Kustiati, Kustiati (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
The catfish culture development program organized by the National Peatland Restoration Agency in 2017 in the Village of Pelita Jaya Indonesia, has a positive impact on the economy. However, there are several obstacles related to the problem of providing catfish juveniles and formulated feed. The Community Partnership Program (PKM) activity aims to increase the income of the â€œSenang Bersamaâ€ Fish Farmers Group through training in catfish spawning techniques and silkworm cultivation. The activity was held in the Village of Pelita Jaya, Kabupaten Kubu Raya, from May to September 2019. The methods used were lectures, demonstrations, training which included hormonal-induced catfish spawning techniques using ovaprim and sludge worm cultivation training. Monitoring and evaluation of activities are carried out starting from the first training until the activity ends. Activity evaluation was carried out using a retrospective (before-after) method using a questionnaire. The training results showed that the activity received a good response from PKM partners with the active participation of the partners and increasing the knowledge and skills of partners in the application of catfish spawning techniques and silkworm cultivation. The PKM partners could practice catfish spawning techniques and silkworm cultivation and apply them to fulfill the needs of group members in terms of catfish juveniles and feed. The impact of the activity as a whole is to develop the independence of the â€œSenang Bersamaâ€ Fish Farmers Group in providing juveniles and natural feed for catfish.